2012
DOI: 10.1073/pnas.1119038109
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 and Akt2 protein kinases differentially contribute to macrophage polarization

Abstract: Activated macrophages are described as classically activated or M1 type and alternatively activated or M2 type, depending on their response to proinflammatory stimuli and the expression of genetic markers including iNOS, arginase1, Ym1, and Fizz1. Here we report that Akt kinases differentially contribute to macrophage polarization, with Akt1 ablation giving rise to an M1 and Akt2 ablation resulting in an M2 phenotype. Accordingly, Akt2 −/− mice were more resistant to LPS-induced endotoxin shock and to dextran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
471
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 484 publications
(493 citation statements)
references
References 30 publications
21
471
0
1
Order By: Relevance
“…This is further supported by a PKB haplodeficient pulmonary fibrosis model [114]. However, in line with M1 activation signals activating PKB, several studies also demonstrate that PKB indeed is critically involved in promoting M1 macrophage activation [115,116]. The clear discrepancy might come from an isoform specific effect of PKB in experimental context.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 80%
See 2 more Smart Citations
“…This is further supported by a PKB haplodeficient pulmonary fibrosis model [114]. However, in line with M1 activation signals activating PKB, several studies also demonstrate that PKB indeed is critically involved in promoting M1 macrophage activation [115,116]. The clear discrepancy might come from an isoform specific effect of PKB in experimental context.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 80%
“…The clear discrepancy might come from an isoform specific effect of PKB in experimental context. Indeed, in an isoform specific deficient model, it is observed that while PKBα inhibits M1 activation and promotes M2 polarization, PKBβ enhances M1 activation and suppresses M2 polarization [115]. Another layer of regulation of macrophage polarization contributed by PKB might come from the downstream effectors.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative macrophage activation, or M2, is characterized by high levels of arginase-1 (Arg-1), found-in-inflammatory zone-1 (Fizz1), chitinase-3-like-3 (Ym1), and macrophage galactose C-type lectin 1 and 2 (MGL1, MGL2) (8,9,19). M2 macrophages participate in the resolution of inflammation and are known to be beneficial in the outcome of several inflammatory diseases (14,(20)(21)(22).…”
mentioning
confidence: 99%
“…The mechanisms that regulate macrophage activation phenotype are currently being investigated (14,21,22). Several signaling pathways, such as STAT-1 phosphorylation, IRF5 upregulation, and SOCS2 and SOCS1 were shown to promote M1 activation (21,(23)(24)(25).…”
mentioning
confidence: 99%